Rosyam Nor : impian jutawan budak setinggan : autograf - Rosyam Nor, 1967-; Abu Salem; Suhan Publication (Kuala Lumpur : Suhan Publication, 2016)
Autobiography of Rosyam Nor, an actor in Malaysia.
In Malay.
Keywords: Rosyam Nor, -- 1967- -- Childhood and youth; Actors -- Malaysia -- Biography; Motion picture actors and actresses -- Malaysia -- Biography; Motion picture producers and directors -- Malaysia -- Biography; Malays (Asian people) -- Malaysia -- Biography; Squatters -- Malaysia -- Kuala Lumpur